MODELING OF THE THERMODYNAMIC PROPERTIES OF TERNARY Ag-Ca-Ge MELTS: DOI: https://doi.org/10.17721/1728-2209.2023.1(58).2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background . Previously, we studied the mixing enthalpies of Ag-Ca-Ge melts at 1300–1550 K in a limited range of composition using the method of high-temperature isoperibolic calorimetry. The topology of isoenthalpies of mixing for the entire range of composition was obtained by modeling according to the theory of regular solution. For a more complete understanding of the nature of the interparticle interaction in these alloys, it is necessary to obtain other thermodynamic functions that are currently missing in the literature. Therefore, modeling of excess Gibbs energies and entropies of mixing of Ag-Ca-Ge melts is relevant. The object of research in the proposed work is the thermodynamic functions of Ag-Ca-Ge melts.Methods . Modeling according to the theory of regular solution using the Redlich-Kister-Muggianu formalism was applied based on information about the constituent systems Ag-Ca(Ge), Ca-Ge and mixing enthalpies of the Ag-Ca-Ge melts taking into account the term of specific ternary interaction. The features of the interaction of unlike components in this ternary system are considered from the point of view of general physicochemical concepts.Results . The excess Gibbs energies and entropies of mixing were modeled for the entire concentration triangle of the Ag-Ca-Ge system at 1400 K. Thanks to the applied calculation method, the authors determined the excess Gibbs energies of mixing of the Ag-Ca-Ge melts, taking into account the term of the specific ternary interaction of the components in this system.Сonclusions . The maximum interaction of unlike components in ternary Ag-Ca-Ge melts falls on the composition region close to the binary boundary Ge-Ca system, with a localization corresponding to congruently melting Ca2Ge and CaGe compounds on the phase diagram of this binary system. With an increase in the silver content in the ternary melt, a gradual decrease in absolute value of the exothermic thermodynamic mixing functions in the direction of the silver angle on the concentration triangle is observed. It is shown that a significant decrease in the calcium content in melts of the ternary Ag-Ca-Ge system contributes to the destruction of the short-range order that exists in the binary Ca-Ge and Ca-Ag alloys, which, in general, reduces the efficiency of interaction of unlike components in ternary melts. The energy of alloy formation in liquid Ag-Ca-Ge alloys is determined by the interaction of unlike components in the constituent system Ca-Ge, the interaction of the components in the Ag-Ca system has a less effect.
Keywords: silver; germanium; calcium; excess Gibbs energies; excess entropies of mixing.